Evaluation of two different approaches to learning shade matching in dentistry - Corcodel, Nicoleta; Karatzogiannis, Efstathios; Rammelsberg, Peter; Hassel, Alexander J. (Acta odontologica Scandinavica, 2012)
Statement of the problem. An important aspect of dental education is teaching and learning shade matching. Objective. To assess the success of two different strategies for learning shade matching. Materials and methods. Seventy-one pre-clinical students (mean age 23; 33.3% men) were divided into two groups. One group (TTB) formed teams of two and they matched three pre-determined teeth on each other using the 3D-Master shade guide. After this exercise, they learned shade matching using a standardized device (Tooth Guide Training Box, TTB) by matching shade tabs in an artificial environment. The other group (GL) matched tooth color in a pre-defined clinical setting in groups of four students. After this, they matched the same teeth as before training, again in groups of two, similarly to group TTB. The reference tooth color was determined by two experienced prosthodontic clinicians. The L*a*b* values for the tabs were provided by the manufacturer and the color difference (ΔE ab) between the chosen tab and the reference was calculated. Linear general estimation equation models were used for statistical evaluation (p = 0.05). Results. In the TTB group, the difference between ΔE ab values before and after training was 0.03, which was not significant (p = 0.927; 95% CI: −0.70/0.77). In the GL group, ΔE ab was 0.98 smaller after training, which was significant (p < 0.001; 95% CI: 0.50/1.50). Conclusion. The ability to match tooth color could be improved by using a group-learning approach in a clinical setting and implementation of such a training session should be considered in undergraduate and postgraduate dental education.
Published online: 27 Jul 2011
Gesehen am 05.10.2018